Fecundidad adolescente, género y desarrollo Evidencias de la investigación - Henao Escovar, Juanita; González, Constanza; Vargas Trujillo, Elvia (Universidad del Rosario, 2010)
This article summarizes several research findings that allow clarifying the relations existing among the teenage fertility, the gender, and the development. First, the overall trends and several consequences and socio-economic, context, and individual factors of the teenage pregnancy phenomenon in Colombia are described. Second, the results of a study in which the authors participated, regarding the incidence, trends, and factors of the teenage fertility in Bogota and Cali are summarized. Next, illustration is provided on how the sexual socialization process promotes the building of rules and gender expectations that affect sex and reproductivedecisions of the female teenagers studied and of their partners. Last, general recommendations are formulated for the design of initiatives addressed to impact the teenage fertility and foster the development from the gender perspective.